THE ANALYSIS OF HEAVY METALS CONTENTS AND MAGNETIC PROPERTIES OF BURIED HORIZONS FROM VYAZIVOK SECTION - MATVIISHYNA, Zh.; DMYTRUK, Yu.; BONDAR, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The feature of heavy metals content and distribution and some magnetic properties of buried soils from Vyazivok section were investigated.